2014
DOI: 10.1176/appi.ps.201300353
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Trends in Psychotropic Medication Use Among Very Young Children in Foster Care

Abstract: Young children who initiated antipsychotic and ADHD medications before the age of six continued to receive them for longer periods of time. There is a critical need for long-term studies to evaluate the effect of chronic exposure on children's health and well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
1
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 18 publications
0
18
1
2
Order By: Relevance
“…Some researchers have argued that psychotropic prescribing patterns for children and adolescents have exceeded the support of clinical research and are beyond the evidence for demonstrating safety and efficacy (Baker, 2018; Bogler et al, 2019; Brenner et al, 2014). To this end, some researchers have called for a reduction in the use of psychotropic medication to treat young children and an increase in studies to evaluate the effect of chronic exposure of such medication on children’s health (dosReis et al, 2014).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Some researchers have argued that psychotropic prescribing patterns for children and adolescents have exceeded the support of clinical research and are beyond the evidence for demonstrating safety and efficacy (Baker, 2018; Bogler et al, 2019; Brenner et al, 2014). To this end, some researchers have called for a reduction in the use of psychotropic medication to treat young children and an increase in studies to evaluate the effect of chronic exposure of such medication on children’s health (dosReis et al, 2014).…”
mentioning
confidence: 99%
“…dosReis et al (2014) conducted a retrospective analysis of psychotropic medication records for a sample of nearly 1,500 foster youth aged 6 years or younger who resided in foster care for at least 1 year. Overall, dosReis et al found that 12% of the children received at least one psychotropic medication over a 3-year period.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Já Bronsard et al (2016), numa metanálise da prevalência de perturbações mentais das crianças e jovens no sistema de proteção, maioritariamente com medida de colocação, estimaram um valor de 49%. De uma forma geral, na investigação neste domínio, os problemas mais frequentemente identificados foram a perturbação de hiperatividade e défice de atenção (PHDA), perturbação de oposição e desafio, depressão, ansiedade e perturbação de stress pós traumático (PTSD) (Desjardins et al, 2017;DosReis et al, 2014;Green, Hawkins e Hawkins, 2005;Linares, Martinez-Martin e Castellanos, 2013;McAuley e Davis, 2009;Narendorf, Bertram e McMillen, 2011).…”
Section: Psicopatologia De Crianças E Jovens Em Contexto Institucionalunclassified
“…Há evidência de que o uso deste tipo de medicamentos é muito frequente neste grupo de crianças e jovens (Zito et al, 2008), sendo duas a três vezes mais elevado comparativamente com a população em geral (Raghavan, Zima, Andersen, Leibowitz, Schuster e Landsverk, 2005). Os diferentes estudos que incidem na prescrição de psicofármacos para este grupo populacional apresentam uma grande amplitude de resultados, entre 12 e 77 % (Brenner et al, 2014;Desjardins, Lafortune e Cyr, 2017;DosReis et al, 2014;Green, Hawkins e Hawkins, 2005;Linares, Martinez-Martin e Castellanos, 2013), podendo esta amplitude de resultados decorrer do tamanho das amostras selecionadas. Em Portugal, de acordo com os relatórios CASA (ISS, 2016; 2017), em 2015, 23,4% das crianças e adolescentes estavam medicados, tendo essa percentagem diminuído para 20%, em 2016.…”
Section: Do Diagnóstico Psicopatológico à Intervenção Farmacológicaunclassified